PENGARUH STRATEGI PRODUK, STRATEGI HARGA TERHADAP EKUITAS MERK DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN DAN LOYALITAS (Studi empiris pasca pembelian AC/Air Conditioner merk Polytron di Kudus) - Kuncoro, 09.42.02.0112 Amin (Students Journal of Economic and Management, 2013)
This study aimed to determine the effect of pricing strategy and product strategy for the brand equity and its impact on purchasing decisions and loyalty. The population in this study is their (consumer) users in the holy AC Polytron with minimal use of one year. Sampling was done by using